2021
DOI: 10.1080/08164622.2021.1964332
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic links between systemic hypertension and open angle glaucoma

Abstract: Systemic hypertension or hypertension is a very common chronic age-related disease worldwide. It is typically characterized by a sustained elevation of blood pressure, particularly when the systolic blood pressure and/or diastolic blood pressure are of more than 140 mmHg and 90 mmHg, respectively. If hypertension is not well controlled, it may lead to an increased risk of stroke and heart attack. It has been shown that hypertension is linked with various ocular diseases, including cataract, diabetic retinopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…Regarding hemodynamics, a notable association between glaucoma and systemic cardiovascular diseases, such as diabetes mellitus (DM) [5][6][7], high blood pressure (BP) [8,9], low BP [10], and nocturnal dipping [11] has been documented, suggesting an elevated incidence of glaucoma in affected individuals. These observations highlight the potential influence of hemodynamic factors on glaucoma development and progression [12,13]. Abnormal vascular function can also influence the secretion and drainage of aqueous humor (AH), thus affecting IOP regulation [14].…”
Section: Introductionmentioning
confidence: 95%
“…Regarding hemodynamics, a notable association between glaucoma and systemic cardiovascular diseases, such as diabetes mellitus (DM) [5][6][7], high blood pressure (BP) [8,9], low BP [10], and nocturnal dipping [11] has been documented, suggesting an elevated incidence of glaucoma in affected individuals. These observations highlight the potential influence of hemodynamic factors on glaucoma development and progression [12,13]. Abnormal vascular function can also influence the secretion and drainage of aqueous humor (AH), thus affecting IOP regulation [14].…”
Section: Introductionmentioning
confidence: 95%
“…As one of the most common cardiovascular diseases, hypertension may have a role on POAG through its effect on IOP, OPP and blood vessel alterations [4][5][6]. Some studies have found that hypertension is associated with higher prevalence and progression of glaucoma [5,7].…”
Section: Introductionmentioning
confidence: 99%